MARINE PROTECTED AREA NETWORK DESIGN: CASE STUDY OF MALUKU PROVINCE - Estradivar; Christian Novia N Handayani; Dirga Daniel; adib Mustofa (COJ (Coastal and Ocean Journal), 2017)
Since 2014, the Ministry of Marine Affairs and Fisheries has started to initate the development of MPA Network in several provinces in Indonesia. The objective of this study is to provide scientific recommendations to the government and stakeholders on MPA Network design that maximizes the ecological functions, protects critical marine habitats and maintains fisheries stocks. Multi-stages spatial analysis and larva connectivity modelling using the best available data in a provincial level were applied. Until December 2015, Maluku Province had seven MPAs with a total of 288,414 ha. Based on spatial analysis, those MPAs had good Replication of critical habitats, but low Representation of critical habitats (3,8% from 20% of ideal representation percentage) that were protected within MPAs. Besides that, only five out of seven MPAs that were connected, i.e. the distance between MPAs is less than 100 km, meanwhile the other two MPAs were isolated from other MPAs. Maluku Province also had several nodes of strong larva connectivity values. This study demonstates the potential to develop an MPA Network in Maluku Province under these several considerations: (1) build new MPAs in several locations such as Buru Island, Maluku Barat Daya, Aru Islands, etc. (2) enlarge the existing MPAs, especially the small size MPAs, and (3) strengthen the roles and functions of management bodies in each MPA and promote an integrated management plan development with all MPA management bodies. Keywords MPA Network, Maluku Province, 3K (Representation, Replication and Connectivity), Larva Connectivity